2009
DOI: 10.1021/jp908239m
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Oxidation of Formic Acid, Methanol, and Ethanol on Electrodeposited Pd-Polyaniline Nanofiber Films in Acidic and Alkaline Medium

Abstract: We present here a simple and direct electrochemical method of depositing a porous Palladium-Polyaniline (Pd-PANI) nanofiber film on conducting surfaces. The one step method consists of the in situ polymerization of aniline in the solution and simultaneous formation of a film of Pd-PANI. The scanning electron microscopy (SEM) images show a dendritic structure and energy dispersive X-ray analysis (EDAX) and XPS confirm the presence of Pd in the nanofiber film. The cyclic voltammetric studies in acid media show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
82
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(83 citation statements)
references
References 61 publications
1
82
0
Order By: Relevance
“…Bai et al [110] supported Pd nanoparticles on polypyrrole-modified fullerene and the Pd/ppy-C60 catalyst showed a good electrocatalytic activity and stability for the oxidation of formic acid. Pd on polyaniline (Pd-PANI) nanofiber film [56], on polypyrrole (PPy) film [111] and PMo12 [112] showed excellent catalytic activity in the oxidation reaction of formic acid in acidic media. Qin et al [113] synthesized highly dispersed and active Pd/carbon nanofiber (Pd/CNF) catalyst which exhibited good catalytic activity and stability for the oxidation of formic acid.…”
Section: Pd Supported On Other Supporting Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bai et al [110] supported Pd nanoparticles on polypyrrole-modified fullerene and the Pd/ppy-C60 catalyst showed a good electrocatalytic activity and stability for the oxidation of formic acid. Pd on polyaniline (Pd-PANI) nanofiber film [56], on polypyrrole (PPy) film [111] and PMo12 [112] showed excellent catalytic activity in the oxidation reaction of formic acid in acidic media. Qin et al [113] synthesized highly dispersed and active Pd/carbon nanofiber (Pd/CNF) catalyst which exhibited good catalytic activity and stability for the oxidation of formic acid.…”
Section: Pd Supported On Other Supporting Materialsmentioning
confidence: 99%
“…Pandey et al [56] deposited a porous Pd-polyaniline (Pd-PANI) nanofiber film on conducting surfaces and the Pd-PANI showed excellent electrocatalytic activity towards the oxidation of ethanol. Su et al [143] prepared Pd/polyamide 6 (Pd/PA6) nanofibers with high surface area using a simple electroless plating method.…”
Section: Pd Supported On Conducting Polymersmentioning
confidence: 99%
“…Palladium (Pd)-based catalysts are attracting major attention as the most viable materials for ADAFCs. [13][14][15][16] The interest in Pd stems from its natural abundance and low-cost compared to Pt (Pd currently sells at half the price of Pt), [17][18][19][20][21][22][23] and enhanced electrochemical kinetics in alkaline media and ADAFCs than Pt catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] It has been demonstrated that palladium exhibit higher electrocatalytic activity than platinum for formic acid electro-oxidation by direction oxidation without adsorbed CO as poisoning species. [ 4 ] Moreover, palladium bimetallic alloys, instead of pure palladium, possess enhanced electrochemical activities because the bimetallic alloys can facilitate desorption of molecule species and result in more surface site availability and thus higher catalytic activity. [ 5 ] For examples, PdSn, Pd 50 Co 50 and PdAu bimetallic catalysts exhibit much higher catalytic activity and stability for electrooxidation of formic acid and ethanol than commercial Pd/C catalyst; [6][7][8][9] and PdFe and PdCu alloys possess enhanced performances in oxygen reduction reaction (ORR).…”
Section: Introductionmentioning
confidence: 99%